2021
DOI: 10.1002/jmd2.12241
|View full text |Cite
|
Sign up to set email alerts
|

Ketotic hypoglycemia in patients with Down syndrome

Abstract: Background: Ketotic hypoglycemia (KH) without an identifiable underlying metabolic or hormonal disease is historically named idiopathic KH. The prevalence is unknown, but idiopathic KH is considered the most frequent cause of hypoglycemia beyond the neonatal period. KH in Down syndrome (DS) has not been reported. Methods:We conducted a web-based survey on KH in DS through the nonprofit patient organization Ketotic Hypoglycemia International. The responses were evaluated for consistency with KH by two authors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…glucagon also had a heterozygous Xp22.23 deletion including GYG2, which protein, glycogenin 2, is substrate for glycogen synthase. Treatment with extended-release cornstarch was effective [18].…”
Section: Resultsmentioning
confidence: 99%
“…glucagon also had a heterozygous Xp22.23 deletion including GYG2, which protein, glycogenin 2, is substrate for glycogen synthase. Treatment with extended-release cornstarch was effective [18].…”
Section: Resultsmentioning
confidence: 99%
“…There also appears to be a higher prevalence of ketotic hypoglycemia in children with DS. 29 Given that an increased frequency of both ketotic and nonketotic hypoglycemia has been reported in children with DS, both within our study (associated with ALL therapy) and outside of our study, we believe that clinicians need to have a higher index of suspicion for the risk of hypoglycemia in children with DS with secondary risk factors for hypoglycemia (including ALL therapy) and that further study needs to be done to better understand the mechanism of both forms of hypoglycemia in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was claimed that IKH is common in African children with chronic malnutrition or severe malaria [12,13]. Drachmann et al [14] found for the first time a high frequency of KH in 10 (7.2%) of 139 Down syndrome (DS) patients, with a median age of 8.0 years, in their study on the prevalence of KH in DS patients. Despite the fact that this result has to be verified in different study contexts.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…This finding warranted verification in different study contexts. The authors suggested screening for KH in DS patients because it is possible to prevent KH attacks, enhance growth, and avoid overeating and obesity with simple therapies such as frequent meals, increased protein intake, and cornstarch consumption [ 14 ].…”
Section: Epidemiologymentioning
confidence: 99%